Microcontroller Based Single Phase Digital Prepaid Energy Meter for Improved Metering and Billing System - Md. Mejbaul Haque; Md. Kamal Hossain; Md. Mortuza Ali; Md. Rafiqul Islam Sheikh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
This paper presents a single phase digital prepaid energy meter based on two microcontrollers and a single phase energy meter IC. This digital prepaid energy meter does not have any rotating parts. The energy consumption is calculated using the output pulses of the energy meter chip and the internal counter of microcontroller (ATmega32). A microcontroller (ATtiny13) is used as a smart card and the numbers of units recharged by the consumers are written in it. A relay system has been used which either isolates or establishes the connection between the electrical load and energy meter through the supply mains depending upon the units present in the smart card.Energy consumption (kWh), maximum demand (kW), total unit recharged (kWh) and rest of the units (kWh) are stored in the ATmega32 to ensure the accurate measurement even in the event of an electrical power outage that can be easily read from a 20×4 LCD. As soon as the supply is restored, energy meter restarts with the stored values. A single phase prepaid energy meter prototype has been implemented to provide measurement up to 40A load current and 230V line to neutral voltage.Necessary program for microcontrollers are written in c-language and compiled by Win-AVR libc compiler.DOI: http://dx.doi.org/10.11591/ijpeds.v1i2.138